Method for preparing nano silica gel from acetic acid deconstruction concrete recycled fine powder

The concrete recycled fine powder is converted into high-purity nanosilica material by acetic acid deconstruction method, which solves the problem of low efficiency in the treatment and reuse of concrete recycled fine powder in the prior art, and achieves an efficient and clean process and a significant improvement in the compressive strength of cement test blocks.

CN119911915APending Publication Date: 2025-05-02SOUTHEAST UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510046012.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The prior art has problems of low efficiency, poor performance and high energy consumption in the treatment and reuse of concrete recycled fine powder, especially in the preparation of efficient nanosilica materials.

Method used

Through the acetic acid deconstruction method, the concrete recycled fine powder in construction waste is converted into high-purity amorphous nano-scale silica gel material. The process includes crushing, screening, impregnation of acetic acid solution, filtration separation and purification.

Benefits of technology

An efficient, clean and green waste treatment process was achieved, and nanosilica materials with small particle size and high purity were prepared, which significantly improved the compressive strength of the cement test block.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119911915A_ABST
    Figure CN119911915A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing nano silica gel from acetic acid deconstruction concrete regenerated fine powder, which comprises the following steps: crushing, screening and grinding industrial wastes of construction wastes to obtain regenerated fine powder, preparing acetic acid analytically pure acetic acid into acetic acid solutions with different concentrations, dipping the regenerated fine powder in the acetic acid solutions, and drying to obtain the nano silica gel. And after the reaction is finished, filtering, drying and purifying to obtain the nano silica gel. According to the method, the regenerated fine powder is subjected to deconstruction treatment through the idea of acetic acid liquid phase separation, the silicon phase in the waste concrete fine powder is extracted through simple and clean process steps, and a high-value deconstruction product is successfully prepared; the method has important significance for finally realizing a perfect closed loop of service-discarding-treatment-cyclic utilization of a concrete cementing material system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, relates to the preparation and application of nano-grade silica gel material, and specifically relates to a method for preparing nano-silica gel by decomposing concrete recycled fine powder with acetic acid. Background Art

[0002] Concrete is the most widely used civil engineering material in the world today. Infrastructure renewal and building reconstruction can generate more than one billion tons of construction and demolition waste every year. As one of the important components of construction waste, waste concrete has problems such as wasting land resources, polluting the environment, low activity and high energy consumption when reused. There have been in-depth discussions and experimental conclusions on the recycled aggregate part, but the treatment process and reuse of the recycled fine powder part are limited.

[0003] At present, the common treatment methods for recycled micropowder include the following aspects: The substitution method uses recycled micropowder to directly replace cementitious materials, but since recycled micropowder is considered to be an inactive substance with no or low cementitious properties, the negative impact on the various properties of the cementitious system becomes increasingly obvious as the amount of substitution increases, so it is not an efficient recycling method. The thermal activation method uses the dehydrated phase obtained by the reverse hydration process of cement to obtain cementitious properties again, but it is necessary to consider many factors including the characteristics of waste concrete (mix design, hydration and carbonization degree), thermal activation method (target temperature, temperature change rate and insulation time), etc., which makes the product discreteness extremely high, resulting in performance differences in new cement-based composite materials. At the same time, there are also problems such as reduced working performance and mechanical properties, high energy consumption and the low-carbon roadmap of energy conservation and emission reduction. In the chemical treatment method, acid solution is usually used to remove or reduce the residual slurry attached to the surface of recycled aggregate, but the role and reuse of recycled fine powder still need further study, and the process steps of similar carbonization method are relatively cumbersome. Therefore, further improvement is needed. Summary of the invention

[0004] To solve the above problems, the present invention discloses a method for preparing nano-silica gel by acetic acid deconstruction of concrete recycled fine powder, wherein the basic silicon phase unit is obtained by liquid phase separation and extraction, and then a high-purity amorphous nano-scale silica gel material is obtained through purification and other processes. The process is simple, scientific, clean and efficient, and a high-value deconstruction product is successfully produced, thereby improving the compressive strength of concrete.

[0005] To achieve the above object, the technical solution of the present invention is as follows: A method for preparing nano silica gel by deconstructing concrete regeneration fine powder with acetic acid, comprising the following steps: (1) crushing, screening, grinding and sieving construction waste and industrial waste to obtain recycled fine powder; (2) Prepare acetic acid solution from analytically pure glacial acetic acid; (3) soaking the regenerated fine powder in an acetic acid solution; (4) treating the suspension after the reaction to obtain a mixed gel and a calcium acetate-rich waste liquid; (5) The mixed gel is purified to obtain nano-scale amorphous silica gel.

[0006] In the step (1), the construction waste and industrial waste are crushed and screened, then ground in a ball mill, passed through a 100-mesh sieve, and then dried in a vacuum drying oven at 140-160° C. to constant weight to obtain regenerated fine powder.

[0007] The concentration of the acetic acid solution in step (2) is 0.84-3.25 mol / L.

[0008] In the step (3), the regenerated fine powder-acetic acid suspension is placed in a magnetic stirrer for a stirring time of 2 to 24 hours.

[0009] In step (3), the mass ratio of the regenerated fine powder to the acetic acid solution is 1:25.

[0010] In the step (4), after the suspension is filtered and separated, the obtained filter residue is washed multiple times with deionized water.

[0011] The purification solution in step (5) is a hydrochloric acid solution with a concentration of 0.3-1 mol / L. The reactant is taken out, filtered, washed, and placed in a vacuum freeze drying oven to dry to constant weight to obtain nano-scale silica gel.

[0012] The present invention discloses a cement test block comprising a regenerated nano silica gel material prepared by the preparation method of the regenerated nano silica gel material according to claim 1, comprising the following components by mass: 611 parts of water, 1162-1210 parts of cement, and 12-60 parts of the regenerated nano silica gel material.

[0013] Technical principle: Cement hydration products will undergo material transformation in an acidic environment, and the type and concentration of the acid will produce different reaction products. Regenerated fine powder (including unhydrated cement clinker, cement hydration products, etc.) can be purified by reaction with acetic acid and other process steps to obtain a solid deconstruction product with high-purity amorphous nano-silica gel material as the main component. Then it can be reused in the cement-based cementitious material system to obtain a recycled nano-silica gel cement-based material.

[0014] The beneficial effects of the present invention are: 1. The present invention transforms the recycled fine powder of concrete in waste building materials through the acetic acid deconstruction method to prepare recycled nano-silica gel materials. The process does not produce toxic and harmful substances, the steps are simple and clean, and it is a green and efficient method for treating waste building waste.

[0015] 2. The silica gel synthesized in the present invention has the characteristics of small particle size, high purity, high specific surface area, etc. Adding a certain proportion of the nano silica gel material of the present invention to the nano modified cement-based material can effectively improve the compressive strength of the cement test block, providing guidance for engineering practice.

[0016] 3. The associated decomposition product, calcium acetate-rich waste liquid, can be reused in the cementitious material system or in the preparation of other high-value products containing calcium phase. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 is the XRD pattern of nano silica gel; Figure 2 is the XRF oxide composition percentage of nanosilica gel; Figure 3 This is the compressive strength diagram of the test block with different dosages of regenerated nano-silica gel (mass percentage of cement replaced). The dosages of the five groups from left to right are 0%, 1%, 2%, 3% and 5%, respectively. The compressive strength data of each group at the age of 3d, 7d and 28d were recorded respectively. DETAILED DESCRIPTION

[0018] The present invention will be further explained below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the following specific embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0019] As shown in the figure, the method for preparing nano silica gel by acetic acid deconstruction of concrete recycled fine powder of the present invention comprises the following steps: firstly crushing and screening construction waste industrial garbage and then grinding them in a ball mill, passing through a 100-mesh sieve and drying them in a vacuum drying oven at 140-160° C. to constant weight to obtain recycled fine powder; preparing acetic acid solution with analytically pure glacial acetic acid in a concentration range of 0-3.25 mol / L; placing the suspension obtained by immersing the recycled fine powder in the acetic acid solution on a magnetic stirrer for 2-24 hours; filtering and separating the suspension after the reaction to obtain a mixed gel; and washing the mixed gel with acid washing and purification and deionized water to obtain nano-scale amorphous silica gel, wherein the concentration of hydrochloric acid used for acid washing and purification is 0.3-1 mol / L.

[0020] The recycled fine powder comes from construction waste and industrial garbage through crushing, screening, grinding and screening. The acetic acid (concentration 99%&) and hydrochloric acid (concentration 36.0%-38.0%) used are both analytical grade and produced by Shanghai MacLean Company. The washing water is deionized water. Example 1

[0021] According to 1m 3 The amounts of various raw materials required for the regenerated nano-silica gel modified cement-based material are as follows: 611 parts of water, 1210 parts of cement, and 12 parts of the nano-silica gel material prepared by the present invention are weighed.

[0022] Place the regenerated nano-silica gel material and cement in an electric concrete mixer for dry mixing for 1 minute, then add them into water for wet mixing, stir at a low speed for 120 seconds, stop for 15 seconds, scrape the cement on the pot wall and blades into the pot, and then stir at a high speed for 120 seconds to obtain the mixed material.

[0023] Add the above-mentioned mixture into the mold in two times, vibrate with a concrete vibrator for 1 minute, then scrape the surface of the mold flat and number it, let it stand indoors for 48 hours, then demould it, put it into a concrete curing box for curing for 28 days. The set temperature of the concrete curing box is 20°C and the set humidity is 95%, and the recycled nano-silica gel modified cement-based material can be obtained. Example 2

[0024] According to 1m 3 The amounts of various raw materials required for the regenerated nano-silica gel modified cement-based material are as follows: 611 parts of water, 1198 parts of cement, and 24 parts of the nano-silica gel material prepared by the present invention are weighed.

[0025] Place the regenerated nano-silica gel material and cement in an electric concrete mixer for dry mixing for 1 minute, then add them into water for wet mixing, stir at a low speed for 120 seconds, stop for 15 seconds, scrape the cement on the pot wall and blades into the pot, and then stir at a high speed for 120 seconds to obtain the mixed material.

[0026] Add the above-mentioned mixture into the mold in two times, vibrate with a concrete vibrator for 1 minute, then scrape the surface of the mold flat and number it, let it stand indoors for 48 hours, then demould it, put it into a concrete curing box for curing for 28 days. The set temperature of the concrete curing box is 20°C and the set humidity is 95%, and the recycled nano-silica gel modified cement-based material can be obtained. Example 3

[0027] According to 1m 3 The amounts of various raw materials required for the regenerated nano-silica gel modified cement-based material are as follows: 611 parts of water, 1186 parts of cement, and 36 parts of the nano-silica gel material prepared by the present invention are weighed.

[0028] Place the regenerated nano-silica gel material and cement in an electric concrete mixer for dry mixing for 1 minute, then add them into water for wet mixing, stir at a low speed for 120 seconds, stop for 15 seconds, scrape the cement on the pot wall and blades into the pot, and then stir at a high speed for 120 seconds to obtain the mixed material.

[0029] Add the above-mentioned mixture into the mold in two times, vibrate with a concrete vibrator for 1 minute, then scrape the surface of the mold flat and number it, let it stand indoors for 48 hours, then demould it, put it into a concrete curing box for curing for 28 days. The set temperature of the concrete curing box is 20°C and the set humidity is 95%, and the recycled nano-silica gel modified cement-based material can be obtained.

[0030] Embodiment 4: According to 1m3 The amounts of various raw materials required for the regenerated nano-silica gel modified cement-based material are as follows: 611 parts of water, 1162 parts of cement, and 60 parts of the nano-silica gel material prepared by the present invention are weighed.

[0031] Place the regenerated nano-silica gel material and cement in an electric concrete mixer for dry mixing for 1 minute, then add them into water for wet mixing, stir at a low speed for 120 seconds, stop for 15 seconds, scrape the cement on the pot wall and blades into the pot, and then stir at a high speed for 120 seconds to obtain the mixed material.

[0032] Add the above-mentioned mixture into the mold in two times, vibrate with a concrete vibrator for 1 minute, then scrape the surface of the mold flat and number it, let it stand indoors for 48 hours, then demould it, put it into a concrete curing box for curing for 28 days. The set temperature of the concrete curing box is 20°C and the set humidity is 95%, and the recycled nano-silica gel modified cement-based material can be obtained.

[0033] Comparative Example 1: According to the amount of each raw material required for 1m3 of regenerated nano-silica gel modified cement-based material, 611 parts of water, 1198 parts of cement, and 0 part of the nano-silica gel material prepared by the present invention were weighed.

[0034] Place the regenerated nano-silica gel material and cement in an electric concrete mixer for dry mixing for 1 minute, then add them into water for wet mixing, stir at a low speed for 120 seconds, stop for 15 seconds, scrape the cement on the pot wall and blades into the pot, and then stir at a high speed for 120 seconds to obtain the mixed material.

[0035] Add the above-mentioned mixture into the mold in two times, vibrate with a concrete vibrator for 1 minute, then scrape the surface of the mold flat and number it, let it stand indoors for 48 hours, then demould it, put it into a concrete curing box for curing for 28 days. The set temperature of the concrete curing box is 20°C and the set humidity is 95%, and the recycled nano-silica gel modified cement-based material can be obtained.

[0036] XRD test was performed on the regenerated nanosilica gel, and the results were as follows: Figure 1 As shown by Figure 1 It can be seen that only an obvious mantou peak appears at around 2θ=24°, and no other obvious crystalline diffraction peaks appear, which indicates that the deconstruction regeneration product is an amorphous material, and the peak position is consistent with SiO2.

[0037] XRF test was performed on the regenerated nanosilica gel, and the results were as follows: Figure 2 As shown in the figure, the main oxide component of the deconstructed waste residue product is SiO2, with a certain amount of Al2O3, and a small amount of impurities such as CaO and Fe2O3. After purification, impurities such as Al are greatly removed, and the purity of the regenerated nano-silica gel can be as high as 99%.

[0038] The compressive strength of the phase change cement-based materials with different dosages of regenerated nanosilica gel in Examples 1-4 (1% in Example 1, 2% in Example 2, 3% in Example 3, and 5% in Example 3) was tested and compared with that of Comparative Example 1 with 0 dosage. The results are as follows: Figure 3 As shown. Figure 3 The results show that for cement-based materials with recycled nano-silica gel added, as the content of recycled nano-silica gel in the system gradually increases from 0% to 5%, at the same age, the compressive strength of the test block first increases and then decreases, and the best effect is achieved when the content is 2%. At this content, the 3d, 7d and 28d compressive strengths of the test block increased by 3.1%, 16.3% and 33.8% respectively. This shows that recycled nano-silica gel can play a good dense filling role, and the presence of recycled nano-silica gel effectively refines the pore structure of cement-based materials, thereby improving the compressive strength of the test block.

Claims

1. A method for preparing nano silica gel by deconstructing concrete recycled fine powder with acetic acid, characterized in that: The following steps are involved: (1) crushing, screening, grinding and sieving construction waste and industrial waste to obtain recycled fine powder; (2) Prepare acetic acid solution from analytically pure glacial acetic acid; (3) soaking the regenerated fine powder in an acetic acid solution; (4) treating the suspension after the reaction to obtain a mixed gel and a calcium acetate-rich waste liquid; (5) The mixed gel is purified to obtain nano-scale amorphous silica gel.

2. The method for preparing nano silica gel from recycled fine powder of concrete deconstructed with acetic acid according to claim 1, characterized in that: The construction waste industrial waste in step (1) is crushed and screened, then ground in a ball mill, passed through a 100-mesh sieve, and then dried in a vacuum drying oven at 140-160° C. to constant weight to obtain regenerated fine powder.

3. The method for preparing nano silica gel from acetic acid deconstructed concrete recycled fine powder according to claim 1, characterized in that: The concentration of the acetic acid solution in step (2) is 0-3.25 mol / L.

4. The method for preparing nano silica gel from acetic acid deconstructed concrete recycled fine powder according to claim 1, characterized in that: In the step (3), the regenerated fine powder-acetic acid suspension is placed in a magnetic stirrer for a stirring time of 2 to 24 hours.

5. The method for preparing nano silica gel from acetic acid deconstructed concrete recycled fine powder according to claim 1, characterized in that: In the step (4), after the suspension is filtered and separated, the obtained filter residue is washed multiple times with deionized water.

6. The method for preparing nano silica gel from acetic acid deconstructed concrete recycled fine powder according to claim 1, characterized in that: The purification liquid in step (5) is a hydrochloric acid solution with a concentration of 0.3-1 mol / L. The reactant is taken out, filtered, washed, and placed in a vacuum freeze drying oven to dry to constant weight to obtain nano-scale amorphous silica gel.

7. A cement test block prepared using the nano silica gel according to claim 1, characterized in that: The composition includes the following components by weight: 611 parts of water, 1162-1210 parts of cement, and 12-60 parts of recycled nano silica gel material.